Learning theory and classroom practice in the lifelong learning sector - Gould, Jim (Achieving QTLS, 2009)
This new book supports trainee teachers in the Lifelong Learning Sector in the understanding and application of learning theories to their classroom practice. Existing teachers in the Lifelong Learning Sector will also find this book an invaluable resource to refresh their knowledge and continue in their personal development. Complex theories are explored in clear and accessible language and the reader is encouraged to use these ideas to develop their own 'theory of learning'. Each learning theory is considered individually and then discussed with the implications for planning, learning and teaching, assessment and classroom management in mind. Points for reflection, teaching and learning activities, summaries and suggestions for further reading are offered throughout the text to reinforce the reader's understanding. This book helps trainees enhance their teaching and develop their professional practice as they work towards QTLS status.